The Role of Traditional Culture in the Formation of Social Identity in Modern Russia - Svetlana, Ivan (International Journal of Social Discussion, 2024)
Traditional culture plays an important role in the formation of social identity in Russia, especially in the midst of the dynamics of rapid modernization. The study aims to explore how elements of traditional culture—such as language, ritual, and art—influence and maintain social identity in modern Russia. This study uses a qualitative approach with literature study methods and in-depth interviews to explore the perceptions of individuals and groups regarding the role of traditional culture in their daily lives. The results of the study show that traditional culture not only functions as a means of identity preservation, but also as a tool of resistance to the influence of globalization and cultural homogenization. These findings show that traditional culture remains relevant and significant in shaping the social structure and collective identity of Russia, despite being in an environment increasingly influenced by modern values. This research contributes to a further understanding of the dynamics between tradition and modernity in the context of social identity formation, as well as emphasizing the importance of preserving traditional culture in the era of globalization.